2011
DOI: 10.1016/j.ympev.2010.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic patchiness in European eel adults evidenced by molecular genetics and population dynamics modelling

Abstract: a b s t r a c tDisentangling the demographic processes that determine the genetic structure of a given species is a fundamental question in conservation and management. In the present study, the population structure of the European eel was examined with a multidisciplinary approach combining the fields of molecular genetics and population dynamics modelling. First, we analyzed a total of 346 adult specimens of known age collected in three separate sample sites using a large panel of 22 EST-linked microsatellit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Due to the absence of obvious barriers, it has been assumed that there were low levels of differentiation in most marine species (Ward et al ., ; Waples, ; Hellberg et al ., ). However, several recent studies have shown that marine populations are more isolated than previously thought (Bahri‐Sfar et al ., ; Cowen et al ., ; Debes et al ., ; Galarza et al ., ; Selkoe et al ., ; Pujolar et al ., ), thus the potential gene flow homogenizing genetic diversity across subpopulations may not be as strong as formerly believed, particularly in fragmented seascapes. The Mediterranean Sea is the archetypal situation where fish species may have isolated subpopulations given the highly tortuous coast with some local semi‐enclosed seas (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…Due to the absence of obvious barriers, it has been assumed that there were low levels of differentiation in most marine species (Ward et al ., ; Waples, ; Hellberg et al ., ). However, several recent studies have shown that marine populations are more isolated than previously thought (Bahri‐Sfar et al ., ; Cowen et al ., ; Debes et al ., ; Galarza et al ., ; Selkoe et al ., ; Pujolar et al ., ), thus the potential gene flow homogenizing genetic diversity across subpopulations may not be as strong as formerly believed, particularly in fragmented seascapes. The Mediterranean Sea is the archetypal situation where fish species may have isolated subpopulations given the highly tortuous coast with some local semi‐enclosed seas (e.g.…”
Section: Introductionmentioning
confidence: 92%
“…shape and size), as well as sampling strategy [1, 5, 10]. While not all of these may apply to marine scenarios, for taxa that employ a broadcast spawning reproductive strategy, consideration of the extent of ocean current-mediated larval dispersal addresses many of these points [4, 2326]. …”
Section: Introductionmentioning
confidence: 99%
“…Philopatry to a single spawning ground and an extensive migration loop with great opportunity for mixing of individuals might explain the homogeneity in genetic composition between geographic areas across Europe, suggestive of a panmictic population (Dannewitz et al, 2005;Als et al, 2011). The observation of a smallscale pattern of genetic patchiness among intra-annual (arrival waves) samples does not conflict with the lack of large-scale geographic substructuring but it is most likely a consequence of a large variation in reproductive success (Pujolar et al, 2006(Pujolar et al, , 2007(Pujolar et al, , 2011a.…”
Section: Introductionmentioning
confidence: 99%